Measuring the harm of sugar sweetened beverages and internalities associated with it - Ding, Ningxin; Desai, Jaikishan (Frontiers in Public Health, 2024)
Introduction Obesity, which is partly driven by the consumption of sugar-sweetened beverages (SSBs), significantly increases the risk of type-2 diabetes and cardiovascular diseases, leading to substantial health and economic burdens. Methods This study aims to quantify the monetary value of health harms caused by SSB consumption, along with the associated internalities, through a contingent valuation survey. The results are crucial for determining the socially optimal tax rate. Results We surveyed 293 residents of Wellington, New Zealand, to assess their willingness to pay (WTP) for reductions in the risks of diabetes, stroke, and heart disease associated with SSB intake. Logistic regression analysis revealed the marginal WTP for a 1% risk reduction in diabetes, stroke, and heart disease to be NZ$404.86, NZ$809.04, and NZ$1,236.84, respectively. Based on these values, we estimate the marginal harm from SSB consumption to be approximately NZ$17.37 per liter in New Zealand, with internalities amounting to NZ$6.43 per liter, suggesting an optimal tax rate of NZ$6.49 per liter. Discussion Implementing such a tax is feasible and would likely double or triple the price of SSBs in New Zealand.